CARRIAGE STATE OF GAβHS AMONG YEMENI SCHOOLCHILDREN AND THE UPPER LIMIT OF NORMAL FOR ASO IN DIFFERENT POPULATION GROUPS - Saleh, Madha (Iraqi Journal of Science, 2024)
The carriage state of Group A beta haemolytic Streptococcus is considered as an important spreading factor for the infection with Streptococcus pyogenes. To investigate that among Yemeni children, 172 apparently healthy school age children were tested by taking throat swab and blood samples. It was found that 15.1% of the total examined children were carrier for GAβHS, compared to 11.05% who were carriers for other groups of β-haemolytic Streptococci. No statistical significant difference was found concerning the age, gender or the area of residency of those children, but, a statistical variation been found when a high family index group was compared to a low family index group among which a higher carriage rate was found in those children from families of more than 6 members. Most GAβHS positive samples showed a positive results with ASO test (92.3%), however, other samples with positive results for non-βHS or non-streptococcal bacteria showed also different degrees for positivity with ASO test (57.9 and 70.8% respectively). The upper limit of normal for ASO titer among different population groups was higher in schoolchildren group (25%) compared to other groups (young adults and adults), and in females compared to males. No significant variation was noticed concerning people living in different areas of residency.